Application of fuzzy PID control to cluster control of viaduct road vibrations - Omurlu, Vasfi Emre; Engin, Seref Naci; Yuksek, Ismail (SAGE PUBLICATIONS LTD, 2008)
Distributed parameter systems have infinite-degrees of freedom. Algorithms for vibration control of these systems have provided satisfactory results for low-frequency ranges but these approaches may cause spillover and undesired conditions at high-frequency ranges resulting in unsatisfactory control performance. In this study, the application of cluster control on viaduct roads composed of flat parts is introduced. Cluster control consists of three stages: sensing, actuation and control of desired mode groups using a control method. Sensing and actuation of mode groups are introduced separately. The grouping and sensing of mode groups are realized by using Finite Element Analysis. Various control architectures, of which the most popular ones are classical PID controllers, have been suggested to apply cluster control for vibrating structures. In this study, a Mamdani-type fuzzy PID controller with two input and two Output is suggested and the system responses, whose dynamics are gathered from a scaled size of a viaduct road, are collected for proposed fuzzy-PID and sliding mode controllers. Analysis of the performance of cluster control along with the individual effects of the controller parameters on system frequency response is discussed and presented.
Keywords: cluster control; fuzzy PID control; sliding mode control; viaduct road vibrations; distributed parameter systems; CONTROL-SYSTEMS; DESIGN; STABILITY; Acoustics; Engineering; Mechanics